Moving too fast? Addressing temporality and acceleration in Portuguese business ventures scaling - Coelho, J. V. (Sociologia, Problemas e Práticas, 2023)
In recent years, Portugal has been increasingly credited as an emergent European entrepreneurial and technological hub, a rising and promising start-up nation. An ethnographic study was developed in one of the most successful start-up ventures operating in Portugal, with the goal of scrutinizing policy effectiveness in an employment creation and relations perspective. Considering the effect temporality regimes and acceleration are increasingly considered to have as new business ventures socioeconomic base, the study focus was placed on speeding-up implications, namely on how actors experience speed as infrastructural base of employment relations.